CREBZF as a Key Regulator of STAT3 Pathway in the Control of Liver Regeneration in Mice. Issue 4 (24th January 2020) - Hu, Zhimin; Han, Yamei; Liu, Yuxiao; Zhao, Zehua; Ma, Fengguang; Cui, Aoyuan; Zhang, Feifei; Liu, Zhengshuai; Xue, Yaqian; Bai, Jinyun; Wu, Haifu; Bian, Hua; et al.
Abstract : Background and Aims: STAT3, a member of the signal transducer and activator of transcription (STAT) family, is strongly associated with liver injury, inflammation, regeneration, and hepatocellular carcinoma development. However, the signals that regulate STAT3 activity are not completely understood. Approach and Results: Here we characterize CREB/ATF bZIP transcription factor CREBZF as a critical regulator of STAT3 in the hepatocyte to repress liver regeneration. We show that CREBZF deficiency stimulates the expression of the cyclin gene family and enhances liver regeneration after partial hepatectomy. Flow cytometry analysis reveals that CREBZF regulates cell cycle progression during liver regeneration in a hepatocyte‐autonomous manner. Similar results were observed in another model of liver regeneration induced by intraperitoneal injection of carbon tetrachloride (CCl4 ). Mechanistically, CREBZF potently associates with the linker domain of STAT3 and represses its dimerization and transcriptional activity in vivo and in vitro . Importantly, hepatectomy‐induced hyperactivation of cyclin D1 and liver regeneration in CREBZF liver‐specific knockout mice was reversed by selective STAT3 inhibitor cucurbitacin I. In contrast, adeno‐associated virus–mediated overexpression of CREBZF in the liver inhibits the expression of the cyclin gene family and attenuates liver regeneration in CCl4 ‐treated mice. Conclusions: These results characterize CREBZF as a coregulator of STAT3 to inhibit regenerative capacity, which may represent an essential cellular signal to maintain liver mass homeostasis. Therapeutic approaches to inhibit CREBZF may benefit the compromised liver during liver transplantation.